2008
DOI: 10.2215/cjn.00310108
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tonsillectomy Plus Steroid Pulse Therapy on Clinical Remission of IgA Nephropathy

Abstract: Background and objectives: Few well-designed investigations have examined how tonsillectomy plus steroid pulse therapy affects IgA nephropathy. A prospective, controlled study therefore was performed to compare the effects of combined therapy with those of steroid pulse alone in patients with IgA nephropathy.Design, setting, participants, & measurements: Fifty-five patients were followed up for 54.0 ؎ 21.2 mo. Thirty-five of them underwent tonsillectomy and steroid pulse therapy (group C), and 20 received ster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
79
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(83 citation statements)
references
References 24 publications
(16 reference statements)
3
79
0
1
Order By: Relevance
“…Hotta et al (2001) found that tonsillectomy combined with steroid pulse therapy reduced proteinuria and improved renal function in IgAN patients during a 5-year follow-up period, though clinical remission rates decreased in parallel with increase in histological score. In addition, Komatsu et al (2008) reported that tonsillectomy combined with steroid pulse treatment can induce clinical remission in patients with IgAN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hotta et al (2001) found that tonsillectomy combined with steroid pulse therapy reduced proteinuria and improved renal function in IgAN patients during a 5-year follow-up period, though clinical remission rates decreased in parallel with increase in histological score. In addition, Komatsu et al (2008) reported that tonsillectomy combined with steroid pulse treatment can induce clinical remission in patients with IgAN.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there have been some reports on the efficacy of tonsillectomy for IgAN in adults and children (Lozano et al 1985;Hotta et al 2001;Kawasaki et al 2006;Komatsu et al 2008). Hotta et al (2001) initially described tonsillectomy with methylprednisolone (MP) pulse therapy (tonsillectomy pulse therapy), which then became a popular approach to treating IgAN for several years in Japan.…”
mentioning
confidence: 99%
“…Tonsillectomy may affect upstream of the pathogenic mechanism by eliminating antigenic stimuli from the tonsillar mucosa. Some Japanese studies have recently reported that tonsillectomy in combination with steroid-pulse therapy can be a more effective therapy for IgA nephropathy than steroid-pulse monotherapy alone [8] or tonsillectomy alone [9,10]. Steroid-pulse therapy can affect downstream of the immunological mechanism by suppressing the abnormal immune response in bone marrow, leading to subsequent inflammation in renal glomeruli [11].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical remission rate treated in the combination therapy group was 86.2% in stage 1 (UP < 0.5 g/day), 73.1% in stage 2 (UP = 0.5-1.0 g/ day), and 43.8% in stage 3 (1.0 g/day < UP and Cr >1.2 mg/ dL in female or > 1.4 mg/dl in male), as opposed to 71.4% in stage 2, and 11.1% in stage 3 in the steroid monotherapy group. Komatsu et al (2008) performed a prospective, controlled study to compare the effects of combination therapy and steroid pulse alone in IgAN patients. Fifty-five patients were followed up for 54 months, i.e., 35 who had undergone tonsillectomy and steroid pulse therapy and 20 who had received steroid pulse monotherapy.…”
Section: ) Steroid Pulse Therapymentioning
confidence: 99%